The Prosperity Gospel: An Investigation Into Its Pros And Cons With Examples Drawn From Zimbabwe - Bishau, David (International Open and Distance Learning Journal, 2015)
The ‘prosperity gospel’ is known by various terms each implying a different set of meanings and characteristics of the gospel. It is sometimes referred to as the ‘health and wealth gospel’ or the ‘prosperity theology’. Both the latter terms bring out certain features of the gospel which we shall discuss in detail below. From the three terms have we identified above there are those that refer to it as ‘gospel’, but others would have problems with identifying it with ‘good news’ and would simply refer to it as a ‘theology’. We agree with those that look at it as a ‘doctrine’ implying that it is a teaching that is derived from the Bible and that emphasizes a particular view, orientation or ideology held firmly by a particular group of Christians. Those that look at it as a form of ‘theology’ do agree with our view point in that they see it as a set of teachings that are systematically derived from the Bible and systematically communicated to a carefully selected audience. Certainly those that look at it as ‘gospel’ look at the prosperity teachings as ‘good news’ that empowers the Christian in some way. Therefore, we may define the term ‘prosperity gospel’ as a set of Christian doctrinal teachings whose basic import or claim is that right from the beginning, it has always been God’s will to bless the Christians financially and that this is so is there in the Bible for all to see. According to the prosperity doctrine the financial blessing is grasped through positive steps of faith. This is why the ‘gospel’ and those who adhere to it have often been viewed in terms of a movement also known in various terms as the Positive Confession Movement or the Word of Faith Movement (See Hank Hanegraaff, 1993 and 2009)
free